Análisis de la organización matemática relacionada con los paralelogramos que se presenta en el texto escolar de primero de secundaria - Caypo Saenz Peña, Joshelyn Nathaly (2022)
The objective of this research is to analyze the mathematical organization related to the topic of parallelograms that is presented in the Secondary Mathematics 1 textbook, prepared by the Norma publishing house and used in public schools in Peru. For this reason, the Anthropological Theory of the Didactic was used. Therefore, the elements of the theory are: Tasks, Techniques, Technology and Theory. In addition, the indicators of completeness of the local mathematical organization will be used. Regarding the methodology, it is qualitative of the bibliographic type. Because articles and master's thesis were taken as a reference to examine the problems related to the mathematical object parallelogram. As a result, it was found that the Secondary Mathematics 1 text, there is a predominance of the know-how block, made up of tasks and techniques. Because, 3 types of tasks were identified with 14 tasks, 14 techniques and only one theory. In addition, the use of the two classifications of De Villiers (1994) was found, being the Hierarchical and Partitional Classification. In relation to the completeness indicators, it is recognized that there are some criteria for the completeness indicators. As a result, completeness occurs partially.